Trading ahead of treasury auctions - Sigaux, Jean-David (Journal of Banking & Finance, 2024)
I develop and test a model that explains the gradual price decline observed ahead of anticipated sales such as Treasury auctions. Risk-averse agents expect a noisy increase in the net supply of a risky asset. They face a trade-off between hedging the noise with long positions and speculating with short positions. As a result of hedging, the price is above the expected price. As the noise decreases, agents hedge less and speculate more, and the price falls. Consistent with these predictions, meetings between the Treasury and dealers and auction announcements explain a 2.4 basis point increase in the yield on Italian Treasuries.